2003
DOI: 10.2741/976
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic viruses for the therapy of brain tumors and other solid malignancies a review

Abstract: In spite of significant advances in the understanding of molecular processes in tumor biology that have led to the development of oncologic therapeutic strategies, the prognosis for several types of tumors (such as brain, pancreas, or hepatic malignancies) remains dismal. Without question, a strong need exists for continued investigations in new agents and new therapeutic regimens. The realization that several genes used by viruses in their lytic life cycle interact and/or complement the function of genes empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Our results show that both soluble TRAIL and membrane-bound TRAIL delivered to the glioma cells by HSV-amplicon vectors have a similar effect on cell killing. Recombinant HSV vectors, for example, deleted for ribonucleotide reductase, (hrR3) have been shown previously to replicate preferentially in and kill tumor cells (Boviatsis et al, 1994;Fulci and Chiocca, 2003). The safety of oncolytic viral therapy depends on the selectivity of viral replication in dividing cell as compared to postmitotic brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that both soluble TRAIL and membrane-bound TRAIL delivered to the glioma cells by HSV-amplicon vectors have a similar effect on cell killing. Recombinant HSV vectors, for example, deleted for ribonucleotide reductase, (hrR3) have been shown previously to replicate preferentially in and kill tumor cells (Boviatsis et al, 1994;Fulci and Chiocca, 2003). The safety of oncolytic viral therapy depends on the selectivity of viral replication in dividing cell as compared to postmitotic brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recruitment of infiltrating monocytic cells has been shown to coincide with clearance of over 80% of HSV-derived oncolytic viral particles [38, 39]. Increased intra-tumoral presence of macrophage/microglia cells has also been reported in human patients treated with adenovirus [40, 41] or HSV-1-derived OV [42] indicating the global significance of macrophages in OV therapy.…”
Section: The Host Response To Ov Therapymentioning
confidence: 99%
“…Oncolytic viruses (OVs) are emerging as important agents in cancer treatment as they offer the attractive therapeutic combination of tumor-selective cell lysis and by acting as potential in situ tumor vaccines (3)(4)(5)(6)(7)(8). Early clinical trials of OVs showed encouraging safety profiles, even at high doses, and with some promising responses, such as the evidence of intratumor viral replication and efficient killing of tumors (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%